2023
DOI: 10.1039/d2ra06989j
|View full text |Cite
|
Sign up to set email alerts
|

Study on ethanol electro-oxidation over a carbon-supported Pt–Cu alloy catalyst by pinhole on-line electrochemical mass spectrometry

Abstract: A carbon supported Pt–Cu electrocatalyst was synthesized by the microwave-polyol method following acid-treatment and physically characterized by different techniques including X-ray diffraction (XRD) and transmission electron microscopy (TEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Zeolite with an ordered micropore structure is considered an ideal support for confining Pt nanoparticles. In addition, it was found that the formation of bimetallic catalysts with other metals such as Cu, Fe, , and Sn , could significantly improve the stability of Pt nanoparticles. Iglesia et al , encapsulated 1–2 nm ultrasmall metal nanoparticles in zeolites via the ligand-stabilized method, which showed an excellent antisintering performance.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite with an ordered micropore structure is considered an ideal support for confining Pt nanoparticles. In addition, it was found that the formation of bimetallic catalysts with other metals such as Cu, Fe, , and Sn , could significantly improve the stability of Pt nanoparticles. Iglesia et al , encapsulated 1–2 nm ultrasmall metal nanoparticles in zeolites via the ligand-stabilized method, which showed an excellent antisintering performance.…”
Section: Introductionmentioning
confidence: 99%